The response of paediatric arrhythmias to intravenous and oral flecainide. Issue 2 (February 1987) - Wren, C; Campbell, R W
Abstract : Flecainide acetate was administered intravenously and orally to 12 consecutive children, aged 1-15 years, presenting with arrhythmias that were life threatening or resistant to conventional medical treatment. Three children had arrhythmias related to Wolff-Parkinson-White syndrome, four had concealed accessory pathways, two had His bundle tachycardia, and three had ventricular tachycardia. Of seven patients who were given flecainide intravenously, four returned to sinus rhythm and in a fifth successful rate control of His bundle tachycardia was achieved. All 12 patients were given the drug orally: in nine it was successful in preventing recurrence of arrhythmia, in one satisfactory rate control was achieved, and in two it was withdrawn because it produced more frequent attacks of tachycardia. No other adverse effects occurred. The efficacy and low toxicity of treatment in this study suggests that flecainide acetate may have an important role in the management of selected paediatric arrhythmias.